125k views
1 vote
Use the rules of exponents to simplify the expressions. Match the expression with its equivalent value.

Use the rules of exponents to simplify the expressions. Match the expression with-example-1

1 Answer

3 votes

Answer/Step-by-step explanation:

1.
((-2)^(-5))/((-2)^(-10))

Apply the Quotient rule: i.e.
(x^n)/(x^m) = x^(n - m)


= (-2)^(-5 - (-10)) = (-2)^5} = -32

2.
2^(-1) * 2^(-4)

Apply the product rule: i.e.
x^n * x^m = x^(n + m).


= 2^(-1 + (-4)) = 2^(-1 - 4)


= 2^(-5)

Apply the negative exponent rule: i.e.
x^(-n) = (1)/(x^n)


= 2^(-5) = (1)/(2^5)


= (1)/(32)

3.
(-(1)/(2))^3 * (-(1)/(2))^2

Apply product rule


= (-(1)/(2))^(3 + 2)


= (-(1)/(2))^(5)


= -(1^5)/(2^5)


= -(1)/(32)

4.
(2)/(2^(-4))

Apply the rules of 1 and quotient rule


= 2^(1 - (-4))


= 2^(1 + 4)


= 2^(5) = 32

User Kavin Raju S
by
5.5k points